La conversion de Durtal dans "La Cathédrale", carrefour de métamorphoses sociales, spirituelles et sémantiques - Kamińska, Aleksandra (2022)
The present paper explores Durtal’s conversion as the refusal of any fixed reference. The reflections of the hero on hispersonal experience, but also on the social transformations are characterised by the metaphysical seriousness andsemantic experiments. The constant lexical substitution arouses the curiosity of the reader: its referential opacity isonly apparent. Thus, the writer emphasizes that going beyond the beaten path requires a new mode of expressionwhere meaning no longer depends on the rehashing of commonplaces, but relies on semantic mismatches andprolonged tensions between juxtaposed terms. Likewise, social transformations strongly disapproved of by thehero become the source of paradoxical reasoning where truth is expressed through the negativity of judgment.Nevertheless, despite the lucidity of his social and ethical judgments, Durtal remains blind to the imperfection ofhis own conversion. Moreover, the frequent recourse to paradox demonstrates that the protagonist is still in doubtwhich announce a long spiritual path of true conversion.
Keywords: conversion; The Cathedral; paradox; semantic experiments; reader